Emotional intelligence from gender perspective during mid to late adolescence in an Indian context - Priya Yogesh Kulkarni; Gajanan Velhal (Wolters Kluwer Medknow Publications, 2023)
Background: Emotional Intelligence (EI) contributes to overall success in life. Our objectives are to explore EI among adolescents and its gender differences as per some parameters of social environments. Material and Methods: Present cross-sectional study was conducted in secondary schools in one of municipal corporations in western Maharashtra EI of adolescents studying in tenth standard in randomly selected secondary schools, was assessed by Schutte's Self-Reported Emotional Intelligence Test with collection of relevant sociodemographic information maintaining confidentiality. Data were analyzed by SPSS 20 software. Results: Total 1060 adolescents in 14-16 years of age participated in the study. Socio-economic status affected EI of adolescent girls more adversely than adolescent boys (P = 0.003, P = 0.036 respectively). Co-educational type of school favored lower EI than gender specific schools (P < 0.001). After gender wise stratification, EI did not differ significantly among boys (P = 0.154) with respect to type of schooling, but differed significantly (P = 0.001) among girls. Conclusion: Apart from continued efforts directed to for improvement in SES, mental health component of school health services needs to take a step forward for assessment and improvement of towards mental health parameters including EI of adolescents. EI training programs commenced in school activities based on gender, socio-economic status and other issues relevant to the situation shall prove beneficial in long run.